The Implementation of Task-Based Language Teaching (TBLT) to Improve Students’ Reading Skills - Sindi Klodia; Budi Budi; Mashuri Mashuri; Sriati Usman (Hasanuddin University, 2025)
This study aims to analyzed the implementation of Task-Based Language Teaching (TBLT) improve the reading skills of the eighth-grade students at SMPN 9 Sigi. The population in this study is all grade VIII students totaling 41 students. This study used a quasi-experimental method where researcher used two classes to get the results of the study, the class was class VIIIA as an control class with 19 students, and class VIIIB as an experimental class with 22 students. The population of this study is all grade VIII students totaling 41 students. The data collection technique used tests in the form of pretests and posttests. Based on the results of the study, the experimental class's students' reading skills significantly improved once the TBLT approach was implemented. This is shown by the calculation using SPSS, the Sig. (2-tailed) value is 0.000 < 0.05. The experimental class obtained a higher post-test average score of 20.06 points compared to the control class. This mean, H₁: The implementation of Task-Based Language Teaching (TBLT) significantly improves the reading skills of eighth-grade students at SMPN 9 Sigi is accepted. Therefore, it can be concluded that there is a difference in the average learning outcomes between the experimental class using the Task-Based Language Teaching (TBLT) model and the control class using the conventional model.